Profiling Students’ Critical Thinking Improvement through PBL E-Worksheet: A Pretest-Posttest Study on Reaction Rate Factors - Dian Novita; Salsa Sabrina Fajar Maulidiah (Universitas Pendidikan Ganesha, 2025)
Field data and previous studies indicate that students’ critical thinking abilities regarding factors influencing reaction rates remain relatively low. This study aims to describe how Problem-Based Learning (PBL), supported by an electronic worksheet integrating multiple chemical representations, enhances students’ critical thinking skills. A descriptive quantitative approach with a one-group pretest–posttest design was employed, involving Grade XI students. Data were gathered through critical thinking tests administered before and after the learning intervention and analyzed based on six critical thinking indicators. The findings revealed significant improvement across all indicators, with the greatest gain observed in interpretation skills. Overall, the results demonstrate that Problem-Based Learning can effectively enhance students' critical thinking skills when combined with multiple chemical representations through an electronic worksheet. This study underscores the importance of innovative and contextually relevant learning tools in developing essential 21st-century competencies in chemistry education.